2008
DOI: 10.3732/ajb.0800068
|View full text |Cite
|
Sign up to set email alerts
|

Sex‐specific responses to mycorrhiza in a dioecious species

Abstract: In most studies about dioecious plants, the role of arbuscular mycorrhizae (AM) and the potential sex-specific differences between the plant hosts have been overlooked. Because plant sexes frequently differ in drought tolerance and AM fungal colonization provides higher resistance to drought, we investigated whether the relation of mycorrhizal fungi with either male or female Antennaria dioica plants differs using a factorial experiment. We hypothesized that because AM usually increase growth rate and male pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
40
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 54 publications
5
40
0
Order By: Relevance
“…In addition, previous studies under greenhouse confirm that the interaction with AM fungi and A. dioica is sex-specific: 15,16 females and males of A. dioica differed in their response to the same AM fungal species (Glomus claroideum). Females gain greater AM benefit than males when grown without stress conditions, while under stress conditions (drought or low pH) the mycorrhizal benefit is lower and similar in both sexes.…”
Section: Dioecious Species and Arbuscular Mycorrhizal Symbiosesmentioning
confidence: 59%
See 3 more Smart Citations
“…In addition, previous studies under greenhouse confirm that the interaction with AM fungi and A. dioica is sex-specific: 15,16 females and males of A. dioica differed in their response to the same AM fungal species (Glomus claroideum). Females gain greater AM benefit than males when grown without stress conditions, while under stress conditions (drought or low pH) the mycorrhizal benefit is lower and similar in both sexes.…”
Section: Dioecious Species and Arbuscular Mycorrhizal Symbiosesmentioning
confidence: 59%
“…Females gain greater AM benefit than males when grown without stress conditions, while under stress conditions (drought or low pH) the mycorrhizal benefit is lower and similar in both sexes. 15,16 These studies suggest that the sexes may provide different amount of photosynthates to the fungus and that they also differ in the benefit derived from the symbiont. However, in natural ecosystems 15 and ii 16 were conducted under greenhouse conditions, while the studies iii 13 and iV 14 were conducted in the field.…”
Section: Dioecious Species and Arbuscular Mycorrhizal Symbiosesmentioning
confidence: 99%
See 2 more Smart Citations
“…In AM symbiosis, nutrients and water are delivered to the plant from the soil whereas the fungi receive carbon in exchange (Smith and Read 1997). It has recently been shown that the sexes of dioecious (Varga and Kytöviita 2008;Varga and Kytöviita 2010a) and gynodioecious plants (Varga and Kytöviita 2010b) may gain sex-specific benefits from their AM symbionts and different patterns of root colonisation have been reported between the sexes of dioecious plants (Eppley et al 2009). This sexual dimorphism between plants and AM fungi has been related to the different resource needs and allocation patterns between the genders (reviewed in Varga 2010).…”
Section: Introductionmentioning
confidence: 99%